Eventstreaming: Connecting streamers and viewers at the Silicon Valley Comic Con - Tang, John; Venolia, Gina; Inkpen, Kori (TVX in Industry 2016, 2016)
Live events are happening all around the world all the time. People are using mobile livestreaming tools (Periscope, Facebook Live, Livestream, etc.) to broadcast those events over video and audio. How can we connect viewers with livestreams of events in which they are interested? How can we help viewers leverage multiple livestreams coming from an event to find the perspective they find interesting? How can we create a user experience that enables them to participate in the event remotely, not just passively watch it? We explored these ideas using commercially available apps and services to eventstream the Silicon Valley Comic Con [4].